Contribution of intravoxel incoherent motion MRI to diffusion-weighted MRI in differentiating benign from malignant breast masses - Rashed, Dina; Settein, Magdy Elsayed Mohamed; Batouty, Nihal M. (Egyptian Journal of Radiology and Nuclear Medicine, 2025)
Background The differentiation of benign and malignant breast masses is a critical aspect of breast cancer diagnosis. The aim of this study was to assess the capability of IVIM variables to discriminate between benign and malignant breast lesions by obtaining diffusion and perfusion data from normal tissues of breast and breast lesions through intravoxel incoherent motion (IVIM) imaging utilising biexponentially analysis of multiple b -value diffusion-weighted imaging (DWI) and comparing these variables to the apparent diffusion coefficient (ADC) derived from monoexponentially analysis. Results In this prospective work, each subject provided informed consent. Forty-two patients with fifty-two lesions with 31 malignancies and 21 benign lesions were scanned using 1.5 T MRI and DWI with 12 b -values (range 0–1000 s/mm 2 ). Tissue diffusivity ( D ), perfusion fraction ( f ), and pseudo-diffusion coefficient ( D p ) were determined by segmented biexponentially analysis. The ADC ( b = 0 and 1000 s/mm 2 ) was computed using monoexponentially fitting of the DWI information. D , f , D p , and ADC values have been acquired for normal tissues of the breast, benign lesions, and malignancies. The contrast of these four variables among each pair indicated that the D and ADC values of malignancies had been substantially lower compared female patients of benign tumours and normal tissues ( P < 0.001). The f of malignancies was substantially greater contrasted to that of benign lesions ( P < 0.001); nevertheless, no substantial variation in D p was seen between both groups. D , f , and values of ADC exhibited superior sensitivity and specificity in distinguishing benign lesions from malignancies, with areas under the curve (AUC) of 0.945, 0.883, and 0.796, correspondingly. At the same time, D p showed the lowest AUC of 0.515. Conclusions IVIM may play a crucial role in differentiating malignancies and benign lesions of the breast by providing separate quantitative measurements of D for cellularity and D p and f for vascularity.